(untitled) (Research, Society and Development, 2024)
This integrative review study aims to compile the main findings related to COVID-19 in computed tomography (CT) to elucidate its relevance as a complementary diagnostic test. The studies were selected from the National Library of Medicine (PubMed) database using the descriptors “Tomography” AND “COVID-19” in September 2024. Review articles, incomplete studies, and those deviating from the proposed design were excluded. A total of 30 articles were identified, of which 8 were deemed eligible for full-text review. Subsequently, 6 studies were selected, and 16 additional articles were included through manual selection to complement the review. The most common tomographic findings were ground-glass opacities and consolidations, with a mixed pattern of these features becoming evident as the disease progressed. The most severe clinical presentations were associated with the appearance of "crazy-paving" (mosaic paving), diffuse ground-glass opacities combined with consolidations in more than two lobes, extensive bilateral pulmonary involvement, increased pulmonary artery diameter, and loss of normal pulmonary architecture. Even after clinical resolution, ground-glass opacities and subpleural bands were still observed, suggesting residual pulmonary impairment. Thus, it can be inferred that CT plays a fundamental role in understanding COVID-19 by demonstrating pulmonary damage at various stages of the disease and aiding in the assessment of severity, although it remains an expensive imaging modality.